Primena veštačke inteligencije kao ključnog elementa za modernizaciju javne uprave - Klaric, Mirko; Boban, Josip Lucijan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
In modern society, public administration is divided into central government administration, local government units and public services established to fulfill various public needs of community users. The purpose of public administration is to solve economic, social and political problems in the community, according to the political decisions in the community. Regulation of Artificial Intelligence, popularly called AI Act has been adopted in the European Union, with the main purpose of regulating general aspects of AI technology implementation. The main approach in the regulation of AI implementation is based on types of risk, which can be predicted by using AI technological solutions. Gradation exists among the four categories of risks in AI technology implementation: unacceptable risk, high risk, limited risk and no risk. Unacceptable risk is connected with AI application which can be dangerous or harmful to citizens’ safety, their rights or livelihoods. The high-risk category of AI implementation influences education, social infrastructure or safety components of market products. The limited AI category of risk defines interaction between humans and AI technological systems, such as chatbots. The lowest category of risk in AI technology implementation is the minimal or no risk category, with implementation of AI technological solutions with minimal influence on humans or social relations, such as spam filters. The future development of AI technology implementation will be regulated according to the common European standards for AI applications. They will be the legal pattern for implementation and control over AI technology beyond EU borders, and contribute to implementation and development of AI application in various aspects of societal life in the European Union and beyond.